Institutional and Financial Incentives for Social Insurance
XI, 242 p.
Keywords: Institutional and Financial Incentives for Social Insurance provides both an empirical and a theoretical account of the main difficulties presently threatening social insurance systems in most industrialized countries. It analyzes the remedies that have been discussed and sometimes introduced and addresses many questions still left largely unresolved: Are newly implemented or proposed reforms providing the correct incentives to all participants in the system? Is the quality of service improving and, if not, what can be done? How should the budgetary problems be solved considering both intra-generational and inter-generational redistributive policies? The volume describes a number of studies of social security systems in various countries and assesses the effect of various policies, including welfare or unemployment benefits, training and other active labour market policies, the provision of pension, and competition and budget devolution in health care. It applies empirical tests to individual preferences concerning unemployment compensation, and it analyzes nonfunded and funded social security systems, the transition from one system to the other, and the willingness to pay for pensions.